1861 : the Civil War awakening - Goodheart, Adam (New York : Vintage Books, 2012)
Chronicles the revolution of ideas that preceded--and led to--the start of the Civil War, looking at a diverse cast of characters and the actions of citizens throughout the country in their efforts to move beyond compromise and end slavery.
Originally published: New York : Alfred A. Knopf, 2011.
Includes bibliographical references (p. [385]-456) and index.
Keywords: United States -- History -- Civil War, 1861-1865 -- Causes; United States -- Politics and government -- 1861-1865.; United States -- Intellectual life -- 19th century